Mathematics Critical Thinking Skills based on Learning Styles and Genders on Brain-Based Learning Assisted by Mind-Mapping - Arifah, Umi; Suyitno, Hardi; Dewi, Nuriana Rachmani (Universitas Negeri Semarang, 2021)
Critical thinking skill in mathematics aims to sharpen calculating skill. It is also to develop higher order critical thinking, such as critical thinking skill. This research aims to find mathematics critical thinking skill patterns based on gender and learning styles: visual, auditory, and kinesthetic. This qualitative method research used sampling technique by using purposive sampling based on gender and high score achievement from each learning style classification of eighth graders of a Junior High School in Semarang. The research instruments cover learning style assessment, mathematics critical thinking skill test, and interview guideline. The findings concluded that male and female students’ mathematics critical thinking skills with visual, auditory, and kinesthetic styles were varied. There were found male and female students with visual, auditory, and kinesthetic styles whose different critical thinking skills in interpreting, analyzing, evaluating, concluding with excellent, sufficiently excellent, and poor categories.